Regulation of Membrane Turnover by Phosphatidic Acid: Cellular Functions and Disease Implications - Thakur, Rajan; Naik, Amruta; Panda, Aniruddha; Raghu, Padinjat (Frontiers in Cell and Developmental Biology, 2019)
Phosphatidic acid (PA) is a simple glycerophospholipid with a well-established role as an intermediate in phospholipid biosynthesis. In addition to its role on lipid biosynthesis, PA has been proposed to act as a signalling molecule that modulates several aspects of cell biology including membrane transport. PA can be generated in eukaryotic cells by several enzymes whose activity is regulated in the context of signal transduction and enzymes that can metabolize PA thus terminating its signalling activity have also been described. Further, several studies have identified PA binding proteins and changes in their activity are proposed to be mediators of the signalling activity of this lipid. Together these enzymes and proteins constitute a PA signalling toolkit that mediates the signalling functions of PA in cells. Recently, a number of novel genetic models for the analysis of PA function in vivo and analytical methods to quantify PA levels in cells have been developed and promise to enhance our understanding of PA functions. Studies of several elements of the PA signalling toolkit in a single cell type have been performed and are presented to provide a perspective on our understanding of the biochemical and functional organization of pools of PA in a eukaryotic cell. Finally, we also provide a perspective on the potential role of PA in human disease, synthesizing studies from model organisms, human disease genetics and analysis using recently developed PLD inhibitors.